Antibiotics and antiseptics for pressure ulcers - Norman, Gill; Dumville, Jo C; Moore, Zena E H; Tanner, Judith; Christie, Janice; Goto, Saori (Cochrane database of systematic reviews, 2016)
Pressure ulcers, also known as bedsores, decubitus ulcers and pressure injuries, are localised areas of injury to the skin or the underlying tissue, or both. A range of treatments with antimicrobial properties, including impregnated dressings, are widely used in the treatment of pressure ulcers. A clear and current overview is required to facilitate decision making regarding use of antiseptic or antibiotic therapies in the treatment of pressure ulcers. This review is one of a suite of Cochrane reviews investigating the use of antiseptics and antibiotics in different types of wounds. It also forms part of a suite of reviews investigating the use of different types of dressings and topical treatments in the treatment of pressure ulcers. To assess the effects of systemic and topical antibiotics, and topical antiseptics on the healing of infected and uninfected pressure ulcers being treated in any clinical setting. In October 2015 we searched: the Cochrane Wounds Specialised Register, the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library), Ovid MEDLINE, Ovid MEDLINE (In-Process & Other Non-Indexed Citations), Ovid EMBASE, and EBSCO CINAHL Plus. We also searched three clinical trials registries and the references of included studies and relevant systematic reviews. There were no restrictions based on language or date of publication or study setting. Randomised controlled trials which enrolled adults with pressure ulcers of stage II or above were included in the review. Two review authors independently performed study selection, risk of bias assessment and data extraction. We included 12 trials (576 participants); 11 had two arms and one had three arms. All assessed topical agents, none looked at systemic antibiotics. The included trials assessed the following antimicrobial agents: povidone iodine, cadexomer iodine, gentian violet, lysozyme, silver dressings, honey, pine resin, polyhexanide, silver sulfadiazine, and nitrofurazone with ethoxy-diaminoacridine. Comparators included a range of other dressings and ointments without antimicrobial properties and alternative antimicrobials. Each comparison had only one trial, participant numbers were low and follow-up times short. The evidence varied from moderate to very low quality.Six trials reported the primary outcome of wound healing. All except one compared an antiseptic with a non-antimicrobial comparator. There was some moderate and low quality evidence that fewer ulcers may heal in the short term when treated with povidone iodine compared with non-antimicrobial alternatives (protease-modulating dressings (risk ratio (RR) 0.78, 95% confidence interval (CI) 0.62 to 0.98) and hydrogel (RR 0.64, 95% CI 0.43 to 0.97)); and no clear difference between povidone iodine and a third non-antimicrobial treatment (hydrocolloid) (low quality evidence). Pine resin salve may heal more pressure ulcers than hydrocolloid (RR 2.83, 95% CI 1.14 to 7.05) (low quality evidence). There is no clear difference between cadexomer iodine and standard care, and between honey a combined antiseptic and antibiotic treatment (very low quality evidence).Six trials reported adverse events (primary safety outcome). Four reported no adverse events; there was very low quality evidence from one showing no clear evidence of a difference between cadexomer iodine and standard care; in one trial it was not clear whether data were appropriately reported.There was limited reporting of secondary outcomes. The five trials that reported change in wound size as a continuous outcome did not report any clear evidence favouring any particular antiseptic/anti-microbial treatments. For bacterial resistance, one trial found some evidence of more MRSA eradication in participants with ulcer treated with a polyhexanide dressing compared with a polyhexanide swab (RR 1.48, 95% CI 1.02 to 2.13); patients in the dressing group also reported less pain (MD -2.03, 95% CI -2.66 to -1.40). There was no clear evidence of a difference between interventions in infection resolution in three other comparisons. Evidence for secondary outcomes varied from moderate to very low quality; where no GRADE assessment was possible we identified substantial limitations which an assessment would have taken into account. The relative effects of systemic and topical antimicrobial treatments on pressure ulcers are not clear. Where differences in wound healing were found, these sometimes favoured the comparator treatment without antimicrobial properties. The trials are small, clinically heterogenous, generally of short duration, and at high or unclear risk of bias. The quality of the evidence ranges from moderate to very low; evidence on all comparisons was subject to some limitations.